A CMOS-based Analog Function Generator: HSPICE Modeling and Simulation - Madina Hamiane (Institute of Advanced Engineering and Science, 2014)
In many Engineering applications, analog circuits present many advantagesover their digital counterparts and have recently been particularly used in awide range of signal processor circuits. In this paper, an analog non-linearfunction synthesizer is presented based on a polynomial expansion model.The proposed function synthesizer model is based on a 10th orderpolynomial approximation of any of the required non-linear functions. Thepolynomial approximations of these functions can then be implemented usingbasic CMOS circuit blocks. The proposed circuit model can simultaneouslysynthesize and generate many different mathematical functions. The circuitmodel is designed and simulated with HSPICE and its performance isdemonstrated through the simulation of a number of non-linear functions.DOI:http://dx.doi.org/10.11591/ijece.v4i4.5981